Two new Hamacantha (Vomerula) from the Rio Grande Rise (SW Atlantic (Hamacanthidae, Porifera) - Castello-Branco, Cristiana; Hajdu, Eduardo (Zootaxa, 2018)
Hamacantha occurs worldwide and frequently in deep-waters. It is easily distinguished from any other sponge by the possession of conspicuous diancistra microscleres. Here we describe two new species from the Rio Grande Rise. Hamacantha (Vomerula) jeanvaceleti sp. nov. is the sole Hamacantha with styles, diancistras in two categories with the smaller ones cyrtancistra-like; and H. (V.) klausruetzleri sp. nov., the sole with two types of megascleres (styles and strongyles), two categories of diancistras, and two categories of sigmas.